Stable isotope‐labelled morphine to study in vivo central and peripheral morphine glucuronidation and brain transport in tolerant mice. (31st August 2018) - Weinsanto, Ivan; Laux‐Biehlmann, Alexis; Mouheiche, Jinane; Maduna, Tando; Delalande, François; Chavant, Virginie; Gabel, Florian; Darbon, Pascal; Charlet, Alexandre; Poisbeau, Pierrick; Lamshöft, Marc; Van Dorsselaer, Alain; et al.
Abstract : Background and Purpose: Chronic administration of medication can significantly affect metabolic enzymes leading to physiological adaptations. Morphine metabolism in the liver has been extensively studied following acute morphine treatment, but such metabolic processes in the CNS are poorly characterized. Long‐term morphine treatment is limited by the development of tolerance, resulting in a decrease of its analgesic effect. Whether or not morphine analgesic tolerance affects in vivo brain morphine metabolism and blood–brain barrier (BBB) permeability remains a major question. Here, we have attempted to characterize the in vivo metabolism and BBB permeability of morphine after long‐term treatment, at both central and peripheral levels. Experimental Approach: Male C57BL/6 mice were injected with morphine or saline solution for eight consecutive days in order to induce morphine analgesic tolerance. On the ninth day, both groups received a final injection of morphine (85%) and d3‐morphine (morphine bearing three 2 H; 15%, w/w). Mice were then killed and blood, urine, brain and liver samples were collected. LC–MS/MS was used to quantify morphine, its metabolite morphine‐3‐glucuronide (M3G) and their respective d3‐labelled forms. Key Results: We found no significant differences in morphine CNS uptake and metabolism between control and tolerant mice. Interestingly, d3‐morphine metabolism was decreased compared to morphine without any interference with our study. Conclusions and Implications: Our data suggests that tolerance to the analgesic effects of morphine is not linked to increased glucuronidation to M3G or to altered global BBB permeability of morphine.